THE READABILITY LEVEL OF THE READING TEXTS IN ENGLISH TEXTBOOK ENTITLED ‘BAHASA INGGRIS X’ - Fariq Shiddiq Tasaufy (Edulitics (Education, Literature, and Linguistics) Journal, 2017)
This research focuses on analyzing the readability level of the selected reading texts in in English textbook entitled Bahasa Inggris X which is used at the tenth grade students of MA Tanwirul Qulub, Sungelebak, Karanggeneng, Lamongan by using cloze test. Meanwhile, there are nine reading texts in textbook and the writer chooses all nine texts to be analyzed because those nine texts include in three types of texts which are required by English curriculum for the tenth grade of senior high school. The texts are descriptive, recount and narrative. The writer finds that there are three texts in fairly easy level and the score is 70 -79. They are My Idol, Issumboshi, The Legend of Malin Kundang. Then, there are three texts in fairly difficult level and the score is 50-59. They are Tanjung Putting, Taj Mahal and Cut Nyak Dhien. Further, there are three texts in difficult level and the score is 30-49. They are Visiting Niagara, The Battle of Surabaya, and B.J. Habibie. Furthermore, the last four texts are include in frustrational level. They are descriptive text entitled Visiting Niagara (42,2 %), recount text entitled B.J. Habibie (36,7 %), recount text entitled Cut Nyak Dhien (40,5 %) and narrative text entitled Issumboshi (32,9 %). These texts consist of many deleted words so the students were confused to fill them. In other word, these texts are difficult to read and understand by the students.Based on the result Flesch Reading Ease Formula, it can be concluded that only three texts are considered as readable texts.